On the Hook: Supporting a Healthy Fishing Future in Massachusetts. - Brown, Margaret; Hung, Ruby; McMahon, Minnie; Nay, Kathleen. (Tufts University. Tisch Library., 2018)
2017 M.A. in Urban and Environmental Policy and Planning Field Project. Client: Fishing Partnership.